Genetic enhancement of neuropathic and inflammatory pain by forebrain upregulation of CREB-mediated transcription - Descalzi Giannina; Fukushima Hotaka; Suzuki Akinobu; Kida Satoshi; Zhuo Min (SAGE Publishing, 2012)
Abstract CREB has been reported to be activated by injury and is commonly used as marker for pain-related plasticity changes in somatosensory pathways, including spinal dorsal horn neurons and the anterior cingulate cortex (ACC). However no evidence has been reported to support the direct role of activated CREB in injury-related behavioral sensitization (or allodynia). Here we report that genetic enhancement of CREB-mediated transcription selectively in forebrain areas enhanced behavioral responses to non-noxious stimuli after chronic inflammation (CFA model) or nerve injury. In contrast, behavioral acute responses to peripheral subcutaneous injection of formalin did not show any significant difference. Furthermore, acute pain responses to noxious thermal stimuli were also not affected. Our results thus provide direct evidence that cortical CREB-mediated transcription contributes to behavioral allodynia in animal models of chronic inflammatory or neuropathic pain.